At the Turn of the Tide: Space Use and Habitat Partitioning in Two Sympatric Shark Species Is Driven by Tidal Phase - Lea, James S. E.; Humphries, Nicolas E.; Bortoluzzi, Jenny; Daly, Ryan; von Brandis, Rainer G.; Patel, Ela; Patel, Evan; Clarke, Christopher R.; Sims, David W. (Frontiers in Marine Science, 2020)
Coexistence of ecologically similar species occupying the same geographic location (sympatry) poses questions regarding how their populations persist without leading to competitive exclusion. There is increasing evidence to show that micro-variations in habitat use may promote coexistence through minimising direct competition for space and resources. We used two sympatric marine predators that show high fidelity to a small, remote coral atoll as a model to investigate how temporally dynamic partitioning of space use may promote coexistence. Using novel methods (difference network analysis and dynamic space occupancy analysis), we revealed that even though blacktip reef sharks Carcharhinus melanopterus and sicklefin lemon sharks Negaprion acutidens both show focused use of the same atoll habitats, the spatio-temporal dynamics of their use was partitioned such that they only shared the same microhabitats 26% of the time. Moreover, the degree of overlap was strongly influenced by the tidal cycle, peaking at ~35% at higher tides as both species appear to target similar intertidal micro-habitats despite the increase in available space. Our work provides a rare example of how two marine predators with similar ecological roles and habitat preferences may coexist in the same place through dynamic segregation of habitat use in space and time, potentially reflecting adaptive behavioural traits for minimising interactions. The strong influence of small tidal variation on species habitat use and partitioning also raises concerns over how atoll ecosystem dynamics may be influenced by sea level rises that could alter tidal dynamics.